Employee motivation and quality of performance in University Libraries - Houaria BOUDJEMAI (Advanced Research in Economics and Business Strategy Journal)
This study analyzes the problem of worker motivation and the quality of performance in university libraries. Because human resource is an important and effective element in any organization, it must therefore be preserved to motivate it, whether financially or otherwise, and it enables a good and effective performance that makes the organization evolve to the highest rank and achieve its goals.